2017
DOI: 10.1103/physrevapplied.8.014032
|View full text |Cite
|
Sign up to set email alerts
|

Ga-Polar (In,Ga)N/GaN Quantum Wells Versus N-Polar (In,Ga)N Quantum Disks in GaN Nanowires: A Comparative Analysis of Carrier Recombination, Diffusion, and Radiative Efficiency

Abstract: We investigate the radiative and nonradiative recombination processes in planar (In,Ga)N/GaN(0001) quantum wells and (In,Ga)N quantum disks embedded in GaN(0001) nanowires using photoluminescence spectroscopy under both continuous-wave and pulsed excitation. The photoluminescence intensities of these two samples quench only slightly between 10 and 300 K, which is commonly taken as evidence for high internal quantum efficiencies. However, a side-by-side comparison shows that the absolute intensity of the Ga-pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…It is likely related to the difference in defect formation mechanics, e.g. higher layer contamination [5,6] for growths in the N-polar orientation by metalorganic vapor phase epitaxy (MOVPE) and by molecular beam epitaxy (MBE) [4,[7][8][9][10], due to the drastically different growth dynamics and chemistry of the N-polar and Ga-polar structures. If the reason for the low IQE of N-polar quantum wells is discovered and solved, and the IQE is brought up to the level of Ga-polar heterostructures, constructing LEDs (or laser diodes) requires placing the quantum wells inside the depletion region of a p-n junction diode.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely related to the difference in defect formation mechanics, e.g. higher layer contamination [5,6] for growths in the N-polar orientation by metalorganic vapor phase epitaxy (MOVPE) and by molecular beam epitaxy (MBE) [4,[7][8][9][10], due to the drastically different growth dynamics and chemistry of the N-polar and Ga-polar structures. If the reason for the low IQE of N-polar quantum wells is discovered and solved, and the IQE is brought up to the level of Ga-polar heterostructures, constructing LEDs (or laser diodes) requires placing the quantum wells inside the depletion region of a p-n junction diode.…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the substrate, it has been found that these NWs mostly exhibited N-polarity, even if a careful chemical pretreatement may in some cases lead to a significant fraction of metal-polar NWs [17 bis]. However, N-polar NWs are intrinsically improper to the realization of efficient devices because of the easy incorporation of impurities on the N-polar surface [18], which motivates the efforts to develop a strategy to convert their polarity from N-polar to metal-polar.…”
mentioning
confidence: 99%
“…Since we know that the internal quantum efficiency (η = τ eff /τ r ) of this reference sample is close to 1 at 10 K, 23 the comparison of the integrated intensities yields η ≈ 0.03 for the N-polar sample at 10 K.…”
mentioning
confidence: 92%
“…Clearly, the decay asymptotically obeys a power law independent of temperature, revealing that recombination occurs between spatially separated, individually localized electrons 6 and holes. 23 In this case, recombination can occur by tunneling and/or diffusion (with a subsequent radiative annihilation of electrons and holes at the same spatial location). With increasing temperature, the decay accelerates (but still follows a power law) and the temporally integrated PL intensity decreases strongly, reflecting the presence of nonradiative recombination.…”
mentioning
confidence: 99%
See 1 more Smart Citation